External and skull morphology of the Andean cat and Pampas cat: New data from the high Andes of Argentina - Tellaeche, Cintia Gisele (2018)
Andean and Pampas cats are 2 Neotropical small felids of the genus Leopardus. Until now, most of the scarce morphometric data published for these felids, especially the rare Andean cat (L. jacobita), were obtained from museum skins and skulls of undetermined sex. Here, we present morphological data from Pampas cats (L. colocolo) and the largest sample of live Andean cats (5 Andean cats and 6 Pampas cats) captured in the Argentine High Andes. We provide a craniometric analysis of all available adult skulls of Andean cats, including the first known female specimens of Andean and Pampas cats (n = 42). We nearly double the number of published external measurements for live Andean cats, and provide measurements and photos of all available skulls of adult Andean cats, including 2 new skulls with known sex. The data show that Andean cats are larger than Pampas cats and morphometric differences may be related to sexual dimorphism in both species. Principal component analysis of skull measurements showed almost complete separation of Andean and Pampas cats.